Health expenditure and utilisation of poor families in a low-income community under the philippine conditional cash transfer program - Mark, A Ryan Gozales, Artemio M (Journal of Health Management, 2024)
Pantawid Pamilyang Pilipino Program (4Ps) is the Philippine version of the conditional cash transfer (CCT) program that measures human development through the provision of conditional cash grants to the poorest of the poor. This research determines the health expenditure and utilisation of the poor families in a low-income community under the CCT program. A cross-sectional research design was adopted using mixed methods of data collection from 177 households between May and June 2017. Results reveal that most families under CCT devote the largest portion of household health expenditure for inpatient health seeking. About 40% of the total expenditure is covered by the National Health Insurance Program and the cost for hospitalisation mostly comes from the out-of-pocket source. Moreover, the common problems encountered during health utilisation and spending are poor customer service of healthcare facilities and uncompensated hospital bill by health insurance.
Keywords: Public health; -- Health utilisation; -- Healthcare facilities; -- Health insurance -- CCT programe